Determinants of capital structure and speed of adjustment to target capital structure: Evidence from US-listed companies - Le, Mai Thi Ngoc (2020)
This study investigates the factors affecting financing decisions and speed of adjustment of U.S. corporations from 2004 to 2015 with nearly 13,000 observations. The difference and system Generalised Method of Moments estimators are applied in the dynamic panel data to control for endogeneity problems. The findings reflect that size and non-debt tax shield experience significant and positive effects on capital structure, while profitability and liquidity show negative influences on total leverage. Furthermore, growth opportunities and uniqueness do not illustrate any pattern in impacting capital structures. The collaterals value of assets indicates weak effects on total leverage, whereas the collateral values and liquidity strongly and positively affect long-term debt.